Distribution and Assemblage Variation of Benthic Macroinvertebrates: A Uniform Elevational Biodiversity Pattern Among Different Groups? - Wang, Baoqiang; He, Yajing; Zhao, Yongjing; Cui, Yongde (Frontiers in Ecology and Evolution, 2022)
Biodiversity patterns along the elevational gradient of vertebrates have been widely focused on in previous studies, but they are still insufficient on invertebrates in lakes to a wide elevational extent. Based on field samplings and literature, we compared biodiversity patterns among different taxonomic groups of benthic macroinvertebrates in 104 lakes of China and India along an elevational gradient of 2–5,010 m a.s.l. and revealed the key driving factors, and then, we discussed the key mechanisms underlying elevational biodiversity patterns. We found that elevational biodiversity patterns of different taxonomic groups were not uniform, e.g., an exponentially decreasing pattern of Bivalvia, a first horizontal and then decreasing pattern of Gastropoda, and a linear decreasing pattern of Oligochaeta and Insecta. Elevation and elevation-controlled variables (temperature and salinity) were the key driving factors to biodiversity patterns. Their effects were strongest on Bivalvia and less on Gastropoda, whereas they were relatively weak on Oligochaeta and Insecta. Finally, we discussed three important mechanisms that shaped elevational biodiversity patterns and assemblage variations of benthic macroinvertebrates by linking our results with the classic hypotheses about biodiversity patterns, including climate/productivity, environmental heterogeneity, and dispersal/history. These results could improve our understanding of biodiversity patterns and biodiversity conservation.